MR angiography compared to conventional selective angiography in acute stroke. - Tomanek, A; Coutts, S; Demchuk, A; Hudon, M; Morrish, W; Sevick, R; Simon, J; Frayne, R; Buchan, A; Hill, MD (2006)
BACKGROUND AND PURPOSE: Accuracy of intracranial magnetic resonance angiography (MRA) and reliability of interpretation are not well established compared to conventional selective catheter angiography. The purpose of this study was to determine the accuracy of MRA in evaluation of intracranial vessels in acute stroke and transient ischemic attack (TIA) patients METHODS: Twenty-nine patients (seven females, 22 males; median age 53) with acute stroke or TIA were enrolled into the study. All patients underwent both MRA using a 3 T clinical magnet and conventional angiography within 48 hours. Median time between MRA and angiography was 263 minutes. Conventional angiography preceded MRA in 15 cases. Fourteen patients received thrombolysis during MRA or angiography. National Institutes of Health Stroke Scale scores were obtained prior to the MR exam. One neuroradiologist rated all conventional angiograms, which were used as gold standard. Five observers, blinded to conventional angiography results and all clinical information except symptom side, rated the MR angiograms. Kappa statistics were used to assess reliability; contingency tables were used to assess accuracy of non-enhanced and enhanced MRA. RESULTS: Two hundred and fifty two intracranial vessels were assessed. Agreement between raters was good for both non-enhanced (kappa = 0.50) and gadolinium-enhanced (kappa = 0.46) images. There were a total of 26 vessels occluded by DSA. Overall, the non-enhanced MRA showed sensitivity of 84.2% (95% CI 60.4-96.6) and specificity of 84.6% (95% CI 78.6-89.4). The enhanced MRA showed sensitivity of 69.2 (95% CI 38.6-90.9) and specificity of 73.6 (95% CI 65.5-80.7). CONCLUSIONS: Magnetic resonance angiography is a good non-invasive screening tool for assessing intracranial vessel status in acute ischemic stroke. Angiography remains the gold standard for definitive assessment of the intracranial circulation.